Identifying the Epileptic Network - Mark Holmes (Frontiers Research Topics, 2014)
An important area of current research in epilepsy focuses on identifying the specific regions within the brain that are affected in individuals with recurring seizures. The epileptogenic process may result not only in pathology in focal cortical regions, but abnormalities in subcortical structures, such as thalamus and basal ganglia, and in intercortical and intracortical connecting white matter pathways. Novel methods of treating refractory epilepsy are urgently needed. The goal of identifying for each affected individual the specific brain regions that are involved offers the promise that novel methods of treatment will one day be developed that specifically target those abnormal regions. Researchers from disparate fields are required to develop and advance this area of research, and this current topic proposes to place a spotlight on the "state of the art" of methods to identify the abnormal networks. Recent work covering a wide variety of disciplines and technologies, including dense array electroencephalography (dEEG), novel methods of analyses of both the interictal dEEG and intracranial EEG (icEEG), magnetoencephalography (MEG), high-resolution magnetic resonance imaging (MRI), functional MRI (fMRI), simultaneous fMRI-EEG, fMRI connectivity measures, simultaneous dEEG-icEEG, and techniques to coregister patient-specific MRI (including white matter pathways) and dEEG, are all examples of areas of research that have contributed to a greater understanding of potential epileptogenic regions. We asked for individuals with expertise in an area of research that expands an understanding of identifying epileptic networks to contribute to this research topic.